A survey of library resources and services in Oyo state secondary schools (2001)
The study examines the provisions of library facilities in Oyo state secondary schools. The population of the study consists of secondary schools in five local Governments, that is, Ogbomoso North, Ogbomoso South, Surulere, Oriire and OgoOluwa local governmnet areas of Oyo state while 45 secondary schools were taken as the study sample. Out of the 45 questionnaires that were adminstered, 75.6% (34) were returned and analyzed. Simple percentage scaores were employed in analyzing the data. Analyses of the fundings revealed that the provision of library facilities in secondary schools is abysmally low if not totally absent. The findings also revealed that only 2 schools have standard libraries with teacher librarians while 22 schools have improvised libraries. Some of these improvised libraries are just been monitored by library prefects. The remaining 10 schools have nothing to show for a library. REcommendations were therefore made to the government, PTA and all those concerned in the provision of secondary school education in nigeria. All concerned should see a well-equiped school library as a priority by providing the necessary funding, supply and organization of materials